Instrumen Penilaian Berbasis Keterampilan Abad Ke-21 untuk Mengukur Kemampuan Literasi Sains Siswa SMA - Yuliasih, Fannie; Sarwi, Sarwi (UPEJ Unnes Physics Education Journal, 2020)
This research aims to decide the quality scores of 21st century skill-based assessment instruments for high school students on the compiled static fluid material; describe the ability of scientific literacy as one aspect of 21st century student skills; and obtain mastery patterns of static fluid concepts. This research used Research & Development model. The research subjects are high school students with total sample of 70 students. The results showed that instrument is valid and high reliability. The results of difficulty index is moderate and the discrimination index is very good. The scientific literacy skills of high school students' on static fluid based on scores still has a very low scientific literacy ability of 58.6%. Understanding the concept of static fluid in high school students based on their scientific literacy abilities starting from the most easier to the difficult ones is the question in category 2 as a way of investigating, category 4 as an interaction of science, technology, and society, category 1 as a body of knowledge and category 3 as a way of thinking.